MommyHood a retractable breastfeeding cover that encourages a more regular breastfeeding practice in public places catered for first-time young mothers - Federico, Jubilee Annie L.
Breastfeeding is widely recognized as the optimal method of infant feeding, offering numerous health benefits for both the mother and child. However, despite its advantages, many women face challenges in practicing breastfeeding, particularly in public spaces due to social stigma and discomfort. This thesis aims to explore the impact of breastfeeding covers as a tool to promote regular breastfeeding practice in public setting.